2022
DOI: 10.1111/jfbc.14078
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA fromSalvia miltiorrhizaexerts anti‐fibrotic effects on cardiac fibroblasts and rat heart tissues by suppressing the levels of pro‐fibrotic factors: The key role of miR‐618

Abstract: Tanshinone IIA (TAN) is widely employed for handling cardiovascular disorders. The current study explored the potential role of miRs in the antifibrotic effect of TAN on heart. Fibrotic features were induced in cardiac fibroblasts (CFs) and in rat hearts, and then handled with TAN. MicroRNAs (miRs) responding to TAN were determined using a microarray assay. The selected miR was modulated to verify its role in antifibrotic effects of TAN. TAN suppressed the viability and the production of α-SMA in CFs, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As the vital regulator in the development of cardiac fibrosis, TGF- β 1 displays a crucial function in enhancing extracellular matrix (ECM) deposition [ 143 , 144 ]. Furthermore, Tan IIA has been suggested to reverse increased levels of collagen type 1 (Col1) and collagen type 3 (Col3), and growing α -smooth muscle actin ( α -SMA) in TGF- β 1 stimulated cardiac fibroblasts (CFs) and acute myocardial infarction (AMI) or HF rats induced by ligating left anterior descending branch (LAD) of the coronary artery through upregulating miR-205-3p [ 145 ], miR-29b [ 146 ], or miR-618 [ 147 ]. It has also been found that Tan IIA was also able to mitigate oxidative stress in HF rats and Ang II-treated CFs to downregulate Col1/Col3, α -SMA, and MMP2/9 [ 148 ].…”
Section: Pharmacological Activities Of Tanshinones On Cvdsmentioning
confidence: 99%
“…As the vital regulator in the development of cardiac fibrosis, TGF- β 1 displays a crucial function in enhancing extracellular matrix (ECM) deposition [ 143 , 144 ]. Furthermore, Tan IIA has been suggested to reverse increased levels of collagen type 1 (Col1) and collagen type 3 (Col3), and growing α -smooth muscle actin ( α -SMA) in TGF- β 1 stimulated cardiac fibroblasts (CFs) and acute myocardial infarction (AMI) or HF rats induced by ligating left anterior descending branch (LAD) of the coronary artery through upregulating miR-205-3p [ 145 ], miR-29b [ 146 ], or miR-618 [ 147 ]. It has also been found that Tan IIA was also able to mitigate oxidative stress in HF rats and Ang II-treated CFs to downregulate Col1/Col3, α -SMA, and MMP2/9 [ 148 ].…”
Section: Pharmacological Activities Of Tanshinones On Cvdsmentioning
confidence: 99%
“…Resveratrol has a strong effect against cardiac fibrosis [ 41 ], and Park Sung-Jun et al [ 42 ] found that resveratrol competitively inhibits phosphodiesterase degradation of cAMP and promotes Epac1 activation. Tanshinone IIA inhibits the expression of α-SMA protein, the NADPH oxidase activity, and oxidative stress involved in myocardial fibrosis [ 43 45 ]. Additionally, it was found that Tanshinone IIA regulates the RAP1 signaling pathway in the study of atherosclerosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its additional cardiovascular effects include antioxidant activity ( Yan et al, 2021 ), anti-atherosclerotic effects (J. Wang et al, 2020a ; Wang et al, 2020b ), protection against myocardial I/R injury ( Li et al, 2023 ; Zhu et al, 2023 ), regulation of lipid metabolism ( Gao et al, 2021 ), anti-fibrotic effects ( Yan et al, 2022 ), vasodilation ( Fan et al, 2011 ), and potential anti-arrhythmic effects ( Shan et al, 2009 ), further demonstrating its multi-faceted role in promoting cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%